Mass distribution of DA white dwarfs in the First Data Release of the Sloan Digital Sky Survey - Madej, J. (2004)
We investigate the sample of 1175 new nonmagnetic DA white dwarfs with the effective temperatures Teff ≥ 12 000 K, which were extracted from the Data Release 1 of the Sloan Digital Sky Survey. We determined masses, radii, and bolometric luminosities of stars in the sample. The above parameters were derived from the effective temperatures Teff and surface gravities log g published in the DR1, and the new theoretical M − R relations for carbon-core and oxygen-core white dwarfs. Mass distribution of white dwarfs in this sample exhibits the peak at M = 0.562 M (carbon-core stars), and the tail towards higher masses. Both the shape of the mass distribution function and the empirical mass-radius relation are practically identical for white dwarfs with either pure carbon or pure oxygen cores.